2016
DOI: 10.2174/1570162x14666160324124558
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of HIV Neuropathogenesis: Role of Cellular Communication Systems

Abstract: Background One of the major complications of Human Immunodeficiency Virus (HIV) infection is the development of HIV-Associated Neurocognitive Disorders (HANDs) inpproximately 50–60% of HIV infected individuals. Despite undetectable viral loads in the periphery owing to anti-retroviral therapy, neuroinflammation and neurocognitive impairment are still prevalent in HIV infected individuals. Several studies indicate that the central nervous system (CNS) abnormalities observed in HIV infected individuals are not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 143 publications
(145 reference statements)
0
48
0
Order By: Relevance
“…This new route of HIV transmission was later confirmed by observations of HIV dissemination in vivo within lymph nodes of humanized mice (24). "Hijacking" of TNTs and other cellular communication pathways by HIV enhances viral transmission to large populations of cells and is considered an important factor in HIV neuropathogenesis and in the establishment of viral reservoirs (25). Moreover, the HIV accessory protein Nef has been shown to stimulate the formation of tunneling nanotubes and virological synapses (26).…”
mentioning
confidence: 89%
“…This new route of HIV transmission was later confirmed by observations of HIV dissemination in vivo within lymph nodes of humanized mice (24). "Hijacking" of TNTs and other cellular communication pathways by HIV enhances viral transmission to large populations of cells and is considered an important factor in HIV neuropathogenesis and in the establishment of viral reservoirs (25). Moreover, the HIV accessory protein Nef has been shown to stimulate the formation of tunneling nanotubes and virological synapses (26).…”
mentioning
confidence: 89%
“…The lateral localization of Cx43 protein and the separation between the different muscle fibers suggest that Cx43 hemichannels may be an additional source of cellular compromise and inflammation as described in other systems. 58,61,62 Opening of Cx43 hemichannels would increase Ca 2þ influx into cardiomyocytes and allow Na þ influx, and K þ efflux and loss of ATP and other metabolites into the extracellular space. In agreement with the suggestion of increased hemichannel opening, our data indicate that all HIV-infected individuals have increased circulation of intracellular molecules transported by the opening of hemichannels.…”
Section: Discussionmentioning
confidence: 99%
“…The development of HIV-Associated Neurocognitive Disorders (HANDs) is one of the major complications of AIDS and cognitive impairment is found in approximately 50-60% of HIV-infected patients [69,70]. It has been shown that HIV-associated deleterious effects in the brain, particularly the neuronal loss is mediated through an increase in connexin 43 expression [71]. Unlike other viruses, HIV is shown to increase the expression of connexin 43 on the astrocytes, which is mainly attributed to the presence of HIV-tat protein.…”
Section: Deleterious Effects Of Connexins In Hiv-induced Dementiamentioning
confidence: 99%